Interdisciplinary knowledge frameworks for transboundary river basins - Gerlak, A. and Saguier, M. (My University, 2015)
A workshop titled Hydroenergy and Climate Change was held in Buenos Aires, Argentina, in July 2014. The goal of the workshop was to identify and frame global change research questions in the context of hydropower development and water-energy futures in South America. Participants included a mix of social scientists, hydrologists, biologists, water engineers, policy specialists and social advocacy actors, all specialized in different aspects of hydroenergy. The main objectives of the workshop included: . generating new knowledge geared toward interdisciplinarity . developing skills and building capacity for local and regional stakeholders and . creating spaces for interaction and collaboration for a diverse set of stakeholders and policy issues related to the governance of transboundary basins. This conference report provides the main findings and some of the important recommendations of the workshop, especially related to emerging interdisciplinary themes around hydropower and climate change in the Uruguay River Basin in South America. We conclude by outlining our next steps to develop good practices for interdisciplinary, user-oriented global change research and develop an interdisciplinary socio-scientific network between natural and social scientists, policy makers and social actors involved in water politics as governance mechanisms and practices.
Keywords: interdisciplinary theme, hydropower, climate change, Uruguay River Basin, South America